Concordance of randomised controlled trials for artificial intelligence interventions with the CONSORT-AI reporting guidelines - Alexander P. L. Martindale; Carrie D. Llewellyn; Richard O. de Visser; Benjamin Ng; Victoria Ngai; Aditya U. Kale; Lavinia Ferrante di Ruffano; Robert M. Golub; Gary S. Collins; David Moher; Melissa D. McCradden; Lauren Oakden-Rayner; et al. (Nature Communications, 2024)
Abstract The Consolidated Standards of Reporting Trials extension for Artificial Intelligence interventions (CONSORT-AI) was published in September 2020. Since its publication, several randomised controlled trials (RCTs) of AI interventions have been published but their completeness and transparency of reporting is unknown. This systematic review assesses the completeness of reporting of AI RCTs following publication of CONSORT-AI and provides a comprehensive summary of RCTs published in recent years. 65 RCTs were identified, mostly conducted in China (37%) and USA (18%). Median concordance with CONSORT-AI reporting was 90% (IQR 77–94%), although only 10 RCTs explicitly reported its use. Several items were consistently under-reported, including algorithm version, accessibility of the AI intervention or code, and references to a study protocol. Only 3 of 52 included journals explicitly endorsed or mandated CONSORT-AI. Despite a generally high concordance amongst recent AI RCTs, some AI-specific considerations remain systematically poorly reported. Further encouragement of CONSORT-AI adoption by journals and funders may enable more complete adoption of the full CONSORT-AI guidelines.